Self-declare halal certification in Langsa city: Empowering MSMEs for quality consumption - Raja, Muhammad; Kurlillah, Anis; Astina, Chahayu; Zulhilmi, Zulhilmi; Fazal Ahmed, Osman Abulkalam (International Journal of Halal Industry, 2025)
Purpose – This study investigates the implementation of self-declared halal certification among Micro, Small, and Medium Enterprises (MSMEs) in Langsa city, Aceh, Indonesia. This research aimed to analyze the process and its impact on fostering dignified and quality consumption within the local community. Methodology – Employing a qualitative field research approach, this study utilized observation, interviews, and documentation as primary data collection techniques. Data were gathered from MSME owners and relevant stakeholders in Langsa city to understand their experience with the self-declared halal certification process. Findings – The findings revealed that implementing self-declared halal certification required educating MSMEs on its significance and procedures. Most MSMEs recognize the necessity for market acceptance and consumer trust. Challenges include limited understanding of processes, scarce resources, insufficient institutional support, and difficulties in documenting halal-compliant raw materials and production. Despite this, certification provided legal assurance of product safety, enhanced business competitiveness, and strengthened consumer trust and satisfaction. Implications – This study highlights the potential of self-declared halal certification as an initial step for MSMEs towards broader halal compliance and their integration into the halal market. However, it also underscores the necessity for enhanced support mechanisms and simplified procedures to maximize its effectiveness in empowering MSMEs and promoting dignified and quality consumption. Originality – This research contributes to the understanding of grassroots-level halal certification implementation and provides valuable insights for the development of more inclusive and harmonized halal standards, particularly for small-scale enterprises.